Comparative anatomical studies on some species of Hyoscyamus L. (Solanaceae) growing in Turkey (Bangladesh Journal of Botany, 2015)
A comparative study based on leaf and stem anatomical structure was made using light microscopy (LM) techniques on five species of Hyoscyamus L. (Solanaceae) in Turkey. Some characters are found important to distinguish the species within the genera. The investigated species can be divided as mesophyll type: bifacial (H. niger L., H. albus L. ) and equifacial (H. aureus L., H. pusillus L., H. reticulatus L.). Druse crystals are recorded only in mesophyll of H. albus. Stomata present on both surfaces, are anisocytic (usually) and anomocytic types. H. reticulatus can be distinguished from other species considering types of trichomes in the stem. Vascular bundles are bicollateral types. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22721 Bangladesh J. Bot. 44(1): 37-43, 2015 (March)